What kind of cities are more conducive to haze reduction: Agglomeration or expansion?. (September 2019) - Zhao, Xin; Shang, Yuping; Song, Malin
Abstract: The realization of high-quality development in the future in China would depend on whether cities, the carriers of China's economic transformation, can create a "win-win" situation in which economic agglomeration and green emission reduction policies are achieved. From the perspective of agglomeration economy theory, this study identified three types of urban forms of 286 prefecture-level cities in China by using night light data, and systematically investigated the effect of urban forms on haze pollution and its influencing mechanism. The research obtained the following findings: (1) under the current level of economic development, higher economic density, a more compact urban form, and a more concentrated single-center mode could effectively reduce particulate matter (2.5) concentration; (2) the mechanism analysis showed that a high-density, single-center or compact urban form plays a role in "haze reduction" by optimizing industrial structure, improving traffic accessibility, and improving the innovation level of enterprises; and (3) further analysis showed that the larger the city size, the easier it would be to cluster the "haze reduction" effect, and it was easier to cluster the "haze reduction" effect in the case of eastern cities than central and western cities.